Membrane technology costs and me - Judd, Simon J. (Elsevier, 2017)
A reflection of the place cost analysis holds in membrane process technology research and development is provided. The review encompassed two membrane processes and applications: (a) reverse osmosis (RO) for seawater desalination, and (b) membrane bioreactor (MBR) technology for wastewater treatment. The cost analysis undertaken extended to (i) the determination of operating expenditure (OPEX) trends using simple analytical expressions, (ii) the subsequent estimation of the sensitivity of OPEX to individual system parameters, and (iii) published data on CAPEX for individual full-scale installations or from cost analyses. An appraisal of the peer-reviewed literature through a survey of a leading scientific database was also carried out. This bibliometric analysis was based on authors’ keywords; it aimed to establish the profile of process cost for each of the two applications when compared with other popular research topics. The OPEX analysis, ostensibly through a consideration of specific energy demand in kWh per m3 permeate, revealed it to relate primarily to hydrodynamics in the case of RO, and to both membrane fouling and air scouring for MBRs. The bibliometric analysis of research trends revealed a marked difference in emphasis on cost aspects between the two research areas, with the focus on cost specifically being 16 times greater for RO desalination of seawater than MBR treatment of wastewater. MBR research appears to be dominated by fouling and foulant characterisation, making up almost a quarter of all studies, notwithstanding evidence from practitioners that other process parameters are as important in determining MBR process OPEX and operability.
Keywords: Reverse osmosis; Membrane bioreactor; Seawater desalination; Wastewater treatment; Fouling; Cost analysis